The Use of Code Mixing In Pak Ndul's Video YouTube Channel - Maksuwel Maksuwel; Yuyun Yulia (Universitas Sarjanawiyata Tamansiswa, 2021)
This research was to find out (1) types of code-mixing and (2) dominant code-mixing level on Pak Ndul’s YouTube video channel. Findings of this research were divided into two parts – types and levels of code-mixing. The types consist of outer and inner utterances revealing 40 and 38 of 51% and 49 % respectively. Regarding levels, the highest percentage of the code-mixing level categories is word level by 54 %, whereas baster and idiom level categories share the lowest percentage on 2.40 %. Keywords: Code-mixing, Qualitative approach, Percentage